Dynamic Event-Triggered Consensus for Multiagent Systems Under DoS Attacks: A Hybrid System Approach - Liu, Guopin; Park, Ju H.; Hua, Changchun; Li, Yafeng (IEEE transactions on systems, man, and cybernetics. Systems, 2023)
In this article, we investigate the consensus problem of multiagent systems (MASs) based on the event-triggered control (ETC) method. The communication between agents is transmitted through unreliable networks with denial-of-service (DoS) attacks. By equipping the MAS with estimation capabilities so as to estimate the lost measurements caused by DoS attacks, we present a hybrid dynamic event-triggered strategy (HDETS) for the consensus of MAS subject to unreliable networks. Based on the proposed HDETS, we can preserve the consensus of MASs provided that the DoS attacks satisfy a condition on its frequency and duration . In addition, it can guarantee the Zeno-freeness with a designed strictly positive minimum event-triggered interval as well. Furthermore, we revisit the estimator with the trigger-resetting property, and present a finite time resetting condition for the estimation error, which illustrates the maximal DoS attacks intensity that the MASs can tolerate. Finally, the developed results are verified by a spacecraft formation simulation example.